Effect of black sesame (Sesamum indicum) and flaxseed flour (Linum usitatissimum) on bread quality using surface response methodology - Rafael Audino Zambelli; Luan Ícaro Freitas Pinto; Edilberto Cordeiro dos Santos; Ana Carolina Viana; Mayara Lima Goiana; Luciana Gamade; Bárbara Guerra Rodrigues (Journal of Engineering & Processing Management, 2018)
The study aimed to evaluate the effect of black sesame andflaxseed flour addition in different proportions on bread quality.The bread formulations were developed through the RotationalCentral Composite Design (RCCD). The independent variableswere: black sesame and flaxseed flour which incorporated inamounts from 25.85% to 54.15%. The effect of the ingredients onbread quality was evaluated through physical parameters (specificvolume, expansion index and volume produced). Statisticalanalysis was performed using response surface methodology andthe two formulations with better technical performance weresubmitted to proximate composition (moisture, protein, fat, ash,carbohydrates and calcium), crumb structure, scanning electronmicroscopy (SEM) and sensorial analysis. It has been found thatblack sesame promotes greater reductions in the mass expansioncapacity than flax meal. There was an improvement in thenutritional value of the loaves by increasing the protein content,ashes, fat and calcium, in addition to the reduction ofcarbohydrates. The breads developed had good acceptability in allevaluated attributes. In this way, the inclusion of black sesameand flaxseed flour as ingredients in bread formulations promotesproducts with technological and sensorial quality.
Keywords: Bread; functional food; quality; SEM